Pemetaan Objek Wisata di Kabupaten Pemalang Berbasis WebGIS - Andi Dwinata; Bita Parga Zen; Eryan Ahmad Firdaus; Firdaus Laia (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
Pemalang Regency, an area rich in tourism potential, needs a system that can map tourist attractions efficiently. In order to meet these needs, WebGIS technology is an attractive solution. With this platform, information about tourist attractions in Pemalang Regency can be accessed easily via the internet, facilitating tourists and the local government to get the necessary information quickly and accurately. The Scrum development method was chosen to build an effective and responsive system, allowing iterative and adaptive development according to user and environmental needs. This research uses a Laravel backend for managing business logic, a React.js front-end for a responsive user interface, and a MySQL database for data storage. The aim of this research is to increase the accessibility of information about tourist attractions in Pemalang Regency via the internet, facilitate tourism promotion, and improve the efficient management of tourism potential. The result is a website that provides geographical information about tourist attractions in Pemalang Regency, which can be accessed online anytime and anywhere. This website makes it easy for users to find information regarding locations, facilities and activities at various tourist attractions. It is hoped that this system can help tourists plan their trips better and assist local governments in more effective tourism promotion. By utilizing modern technology and structured development methods, this system will provide an interactive and satisfying user experience. Its implementation is expected to have a positive impact on the local tourism industry and the economic growth of Pemalang Regency as a whole. This is an effort to combine information technology with the tourism sector to create sustainable and competitive solutions in today's digital era